A Systematic Review of risk factors for major adverse cardiovascular events in patients with coronary heart disease who underwent percutaneous coronary intervention - Zhai, You; Shang, Hongcai; Li, Yan; Zhang, Nan; Zhang, Jisi; Wu, Shangwen (Frontiers in Physiology, 2025)
ObjectiveThis study aims to systematically review the risk factors for major adverse cardiovascular events (MACE) in patients with coronary heart disease who have undergone percutaneous coronary intervention (PCI).DesignSystematic review and meta-analysis.Data sourcesThe Cochrane Library, PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Database, and VIP Database for Chinese Technical Periodicals (VIP) were screened until December 2024.Eligibility criteria for selecting studiesCase-control studies or cohort studies on the risk factors for MACE in patients with coronary heart disease who underwent PCI. Data extraction and synthesis: The literature review, data extraction, and quality evaluation were conducted by two independent researchers, and the meta-analysis was performed using RevMan 5.4 software.Main outcomesThe main outcome was that MACE occurred during the follow-up period.ResultsA total of 40 articles were included. The meta-analysis erevealed that dyslipidemia (OR = 1.50; 95% CI [1.19, 1.89], p = 0.0007), diabetes mellitus (OR = 1.70; 95% CI [1.43, 2.02], p < 0.00001), hypertension (OR = 1.62; 95% CI [1.35, 1.96], p < 0.0001), history of smoking (OR = 2.08; 95% CI [1.51, 2.85], p < 0.0001), poorer ventricular function (OR = 2.39; 95% CI [2.17–2.64], p < 0.0001), impaired left ventricular ejection fraction (LVEF) (OR = 1.86; 95% CI [1.71–2.03], p < 0.0001), door to balloon (D-to-B) time (OR = 0.61; 95% CI [0.42–0.88]; p = 0.009), thrombolysis in myocardial infarction (TIMI) (OR = 1.41; 95% CI [1.17, 1.70], p = 0.0004), renal dysfunction (OR = 1.82; 95% CI [1.37, 2.43], p < 0.0001), and multi-vessel coronary artery disease (OR = 0.41; 95% CI [0.37, 0.46], p < 0.0001) were significantly associated with MACE after PCI.ConclusionThe independent risk factors of MACE after PCI are dyslipidemia, hypertension, diabetes mellitus, smoking history, Killip class > II, LVEF ≤40%, D-to-B time >90 min, TIMI flow grade ≤ II, renal insufficiency, and multivessel disease.